The complications : on going insane in America - Rensin, Emmett (Harper One, an imprint of HarperCollins Publishers, 2024)
Emmett Rensin shares a portrait of what it's like to live with schizoaffective disorder of the bipolar type as well as a critique of America's mental health culture. Going beyond pure memoir, Rensin reflects on the uncertain "science" of diagnosis, the nature of art about and by the insane, political activism, and the history of madness, from the asylum to the academy.